Evaluation of the cytotoxic and genotoxic potentials of the solubilized extract of the coffee waste using Allium cepa as a test system - Siqueira, Priscyanne Barreto; Lima, Viviane Moreira de; Almeida, Thuanny Moares de; Franco, Heider Alves; Borba, Hélcio Resende; Thode Filho, Sérgio (Ciência e Natura, 2018)
The residual biomasses of coffee and other beverages generated in coffee shops, restaurants, residences, bars among others do not have registers due to the difficulty of quantifying this type of waste in different places. To analyze the toxic effects for substance or mixed substances improperly discarded should be performed toxicity tests that aim to predict the potential impact of a xenobiotic on the environment. The objective of this work was to evaluate the impact of the solubilized extract of coffe waste on the germination and development of onion seedlings (A. cepa), as well as to evaluate the cytotoxic and genotoxic potential of this extract in onion root meristematic cells. The experimental design was completely randomized, consisting of five treatments for the test group and two control group. For all treatments, 5 replicates were used. To evaluate the cytotoxicity and genotoxicity test, 5 seedlings of each treatment were removed after the germination process. Thus, from the treatment T2, the extract was able to provide a deleterious effect on germination and root growth. The extract presented a genotoxic effect in the concentration of T2 to T5 treatments, and in addition to genotoxicity, T3 to T5 treatments also showed a cytotoxic effect.